Prediction of Biochemical Recurrence-Free Survival of Prostate Cancer Patients Leveraging Multiple Gene Expression Profiles in Tumor Microenvironment - Zhou, Rui; Feng, Yuanfa; Ye, Jianheng; Han, Zhaodong; Liang, Yuxiang; Chen, Qingbiao; Xu, Xiaoming; Huang, Yuhan; Jia, Zhenyu; Zhong, Weide (Frontiers in Oncology, 2021)
Tumor-adjacent normal (TAN) tissues, which constitute tumor microenvironment and are different from healthy tissues, provide critical information at molecular levels that can be used to differentiate aggressive tumors from indolent tumors. In this study, we analysed 52 TAN samples from the Cancer Genome Atlas (TCGA) prostate cancer patients and developed a 10-gene prognostic model that can accurately predict biochemical recurrence free survival based on the profiles of these genes in TAN tissues. The predictive ability was validated using TAN samples from an independent cohort. These ten prognostic genes in tumor microenvironment are different from the prognostic genes detected in tumor tissues, indicating distinct progression-related mechanisms in two tissue types. Bioinformatics analysis showed that the prognostic genes in tumor microenvironment were significantly enriched by p53 signalling pathway, which may represent the crosstalk tunnel between tumor and its microenvironment, and pathways involving cell-to-cell contact and paracrine/endocrine signalling. The insight acquired by this study has advanced our knowledge of the potential role of tumor microenvironment in prostate cancer progression.